Relationship between anxiety and insomnia in clinical clerkship students during COVID-19 pandemic - Maria Sekartaji; Resty Puspita Sari; Muhammad Irsan; Muhammad Adnan; Labitta Pachira Aquaira; Shabrina Rifka Farahiya; Firdaus Hafidz (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2021)
During the COVID-19 pandemic, there is an increase in anxiety disorder towards the general population, including those clinical clerkship students who are associated with health care services. There has been limited study conducted regarding to the topic, especially during the COVID-19 pandemic. This study was aimed to know the prevalence of anxiety and insomnia, as well as the correlation between them, in clinical clerkship students during COVID-19 pandemic. An online survey was conducted using a cross-sectional approach to 229 clinical clerkship students batch 2015 at the Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada. This study used the Insomnia Severity Index (ISI) and General Anxiety Disorder-7 (GAD-7), administered using Google Forms. Data were analysed using the Chi-Square test. We collected 101 responses. There were 41.6% of males and 58.4% of females with ages ranging from 21 to 26. The result shows 26.7% (95% CI: 8.1-35.4%) of students undergo anxiety and 44.6% (95% CI: 34.9-54.3%) of students experienced insomnia throughout the COVID-19 pandemic. There is a correlation between anxiety and insomnia on clinical clerkship students during the COVID-19 pandemic. Clinical clerkship students with an anxiety disorder have 2.62 times greater risk of experiencing insomnia (p<0.001). The correlation between insomnia and anxiety during COVID-19 pandemic is vital because clinical clerkship students are directly involved in health care services and could risk the safety of patients. Thus, it is important to conduct the course of actions to reduce the risk of mental health problems during pandemic conditions. Also, further research is needed to have a better understanding of the impact on learning performance.